Development of E-Module Using ROPES Strategy Assisted with Sigil Software to Improve Students’ Critical Thinking Skills - Sugiarto, Agus; Sartika, Rody Putra; HL, Nur Ihsan; Syarifuddin, Syarifuddin (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This study aims to develop an E-module with the ROPES (Review, Overview, Presentation, Exercise, summary) strategy assisted by Sigil software on elasticity and Hooke’s Law to improve the critical thinking skills of class XI high school students that are valid, practical and effective. This method of research and development with the ADDIE model. The research instrument consisted of pretest-posttest questions, validation sheets, learning implementation sheets, teacher response questionnaires, and student responses. Data analysis techniques were analyzed descriptively and inferentially. The results of the study were known: 1) the validation results by three educational expert validators on the E-module with the ROPES strategy assisted by Sigil software are declared valid in terms of constructs and content with an average score of 0.85 in the very valid category so that it can be applied in learning activities, 2) the practicality of the E-module with the ROPES strategy assisted by Sigil software was measured by learning implementation sheets and questionnaires for teacher and student responses. The implementation sheet showed the average score for the limited trial class of 3.5 with the good category and the broad trial class of 3.65 with the very good category. The student response questionnaire showed the mean score for the limited trial was obtained at 83.5%, which was included in the very good category, and the broad trial and 87%, which was included in the very good category, and the teacher response questionnaire showed the average score for the limited trial. Furthermore, the broad test obtained an average result of 83% with the category very good, so the e-module was practical for learning at school. 3) the effectiveness of the E-module with the ROPES strategy assisted by Sigil software in terms of pretest-posttest questions obtained the criteria for the limited test N-Gain value of 0.68 with the Medium category and the broad test N-Gain 0.71 with the High category, supported by independent test results -samples-test which shows that there is a significant difference in learning achievement before and after using the E-module. It is concluded that the E-module with the ROPES strategy assisted by Sigil software effectively improves students’ critical thinking skills in learning.